Kenyan Universities: On the Brink of Financial Insolvency - Munene, Ishmael (International Higher Education, 2019)
The financial crisis engulfing Kenyan universities has impacted operations and raised doubts about long-term sustainability. This crisis has a double impetus: at the national level, policy changes impacting the entire system, and at the institutional level, challenges in terms of financial governance. A short-term solution requires an immediate infusion of cash, but a long-term strategy entails a multipronged reform in the financing of higher education at national and institutional levels.